In Silico Testing of Cocoa Pod Husk (Theobroma cacao L.) and Kersen Leaves (Muntingia calabura L.) Extracts as Candidate Drugs for Type 2 Diabetes - Damayanti Abdul Karim, Dewi; Mayola Pisacha, Iga; Safutri, Wina (Universitas Aisyah Pringsewu, 2024)
Diabetes mellitus is a metabolic disorder caused by elevated blood glucose levels. The incidence of diabetes mellituscontinues to rise globally, including in Indonesia. Type 2 diabetes mellitus is the most common type due to the inabilityof pancreatic beta cells to produce sufficient insulin. Kersen leaves (Muntingia calabura L.) and cocoa pod husk(Theobroma cacao L.) are natural ingredients rich in quercetin and are widely found in Indonesia. A higher quercetincontent correlates with its potential as an antidiabetic candidate. The aim of this research is to develop a standardizedcomprehensive herbal medicine from a combination of cocoa pod husk extract and kersen leaves extract, which isexpected to produce more potent antidiabetic activity with a clearly understood mechanism. This research employs anexperimental laboratory method, including in silico testing, to determine the target proteins of bioactive compounds andanalyze their interactions with alpha-glucosidase and GLUT4, as well as to obtain preliminary toxicity data. The in silicoresults show that quercetin has the best binding affinity compared to natural AGI ligands and GLUT4 targetmacromolecules. There is no amino acid residue similarity interaction was found between quercetin and the targetmacromolecules of AGIs and GLUT4, suggesting that quercetin may potentially bind to eNOS and HIF-1? receptors. Thepharmacokinetic predictions indicate that quercetin has a good pharmacokinetic profile, as it meets several of Lipinski'sRule of Five criteria, making it suitable for oral use.